Evolution by natural selection is a scientific law and not just a theory - Daniel J.M. Crouch; Walter F. Bodmer (Academia Biology)
The concept of evolution by natural selection was developed primarily by Darwin and Wallace in the 19th century as an explanation for the diversity and origin of complex organisms. They, however, did not have access to a mechanism of inheritance, which was needed for a proper understanding of how evolution by natural selection could work. Mendel’s discovery of the basic laws of inheritance in diploid sexual organisms enabled Fisher, Haldane, and Wright to provide a theoretical framework for understanding the selective process of evolution by natural selection. The developing knowledge of prokaryotic microorganisms and the discovery of DNA or RNA as the fundamental basis of inheritance in all living organisms, together with Mendel’s laws, now provide the four basic conditions for evolution by natural selection, namely reproduction that is stable, but allows for variation that can increase fitness in the broadest sense. These definitive conditions establish an exponential growth law for evolution by natural selection that applied initially for the longest period of time to the evolution of asexual clonal organisms, and through Mendel's laws, extends to bisexual multicellular organisms. It is mistaking evolution by natural selection to be a scientific theory rather than a law that has led to unnecessary disagreements over its fundamental validity and explanatory power.